Inquiry-based learning for science, technology, engineering, and math (STEM) programs a conceptual and practical resource for educators - Blessinger, Patrick; Carfora, John M. (Innovations in higher education teaching and learning ;, 2015)
Inquiry-based learning (IBL) is a learner-centered active learning environment where deep learning is cultivated by a process of inquiry owned by the learner. It has roots in a constructivist educational philosophy and is oriented around three components: 1) exploration and discovery (e.g. problem-based learning, open meaning-making), 2) authentic investigations using contextualized learning (e.g. field studies, case studies), and 3) research-based approach (e.g. research-based learning, project-based learning). IBL begins with an authentic and contextualized problem scenario where learners identify their own issues and questions and the teacher serves as guide in the learning process. It encourages self-regulated learning because the responsibility is on learners to determine issues and research questions and the resources they need to address them. This way learning occurs across all learning domains. This volume covers many issues and concepts of how IBL can be applied to STEM programs. It serves as a conceptual and practical resource and guide for educators, offering practical examples of IBL in action and diverse strategies on how to implement IBL in different contexts.